Molecular epidemiology of the measles virus in the region of the Americas: Current Overview - Aguilar Gamboa, Franklin Romulo (2020)
Introduction: Measles is one of the most contagious diseases that affect humans. After its eradicationin the Americas region in 2016, it has reemerged and the number of cases is progressively increasing..Objective: To deepen and update the most important aspects of the measles virus molecularepidermiology in the Americas. Methods: The search and analysis of the information was carriedout over a period of five months (November 1, 2019 to March 31, 2020) for which the following wordswere used: measles, molecular epidemiology, America, outbreak, genotype, epidemic, in the PubMed,Hinari, SciELO and Medline databases Likewise, the epidemiological reports of the Pan American HealthOrganization (PAHO) and government entities from different countries of America were taken intoaccount. Results: Two lineages of the D8 genotype are spreading widely in the Americas region. Andalthough we still cannot know the impact of the current pandemic produced by the SARS-CoV-2, thelow immunization rate, the high migratory movements before 2020, socio-cultural and religious factorsadded to the social and political crisis that affect to some countries in the region, they are helping toincrease this problem. Conclusion: The review provides knowledge of the molecular epidemiologyof the virus. Its use and correct interpretation will allow establishing adequate management andcontainment measures in order to recover the eradicated disease condition in the Americas.